2003
DOI: 10.1053/jhep.2003.50350
|View full text |Cite
|
Sign up to set email alerts
|

High body mass index is an independent risk factor for nonresponse to antiviral treatment in chronic hepatitis C

Abstract: The aim of this study was to determine if body mass index (BMI) was an independent predictor of response to antiviral treatment in patients with chronic hepatitis C. A retrospective review was performed of all patients at a single center with chronic hepatitis C treated with antiviral medication from 1989 to 2000. A sustained response was defined as either negative hepatitis C virus (HCV) RNA by polymerase chain reaction and/or normal alanine aminotransferase (ALT) level (only in those treated before availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
228
3
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(258 citation statements)
references
References 30 publications
16
228
3
11
Order By: Relevance
“…However, in subjects with viral genotype 3, steatosis does not negatively affect the outcome of treatment, suggesting that steatosis per se may not intrinsically impair antiviral efficacy. Other investigators found that obesity is a negative predictor of treatment response, 60 and in an earlier study, interferon blood levels and 2Ј5Ј-oligoadenylatesynthetase induction were lower in obese patients after a dose of interferon-␣. 61 Because obesity and steatosis are inter-related, whether their effects are independent and whether weight-based dosing can improve the treatment response remain unclear.…”
Section: Steatosis and Response To Antiviral Therapymentioning
confidence: 68%
See 1 more Smart Citation
“…However, in subjects with viral genotype 3, steatosis does not negatively affect the outcome of treatment, suggesting that steatosis per se may not intrinsically impair antiviral efficacy. Other investigators found that obesity is a negative predictor of treatment response, 60 and in an earlier study, interferon blood levels and 2Ј5Ј-oligoadenylatesynthetase induction were lower in obese patients after a dose of interferon-␣. 61 Because obesity and steatosis are inter-related, whether their effects are independent and whether weight-based dosing can improve the treatment response remain unclear.…”
Section: Steatosis and Response To Antiviral Therapymentioning
confidence: 68%
“…8 The development of cirrhosis in patients with HCV may be associated with regression of steatosis, 21 as has previously been documented in non-alcoholic steatohepatitis (NASH). 22,23 The mechanisms leading to a reduction in steatosis in the liver with cirrhosis remain Mihm et al 99 Yes Ratziu et al 18 Yes Fartoux et al 19 Yes Czaja et al 9 Yes Yes Yes Hourigan et al 10,11 Yes Yes Yes Adinolfi et al 12 Yes Yes Yes Yes Westin et al 13 Yes Weak Yes Yes Castera et al 14 Yes Yes Monto et al 15 Yes Yes Yes Kumar et al 100 Yes Camps et al 101 Yes (BMI) Kaserer et al 102 Yes Bressler et al 60 Yes (BMI) Rubbia-Brandt et al 28 Yes Yes Poynard et al 16 Yes Yes Yes Yes Yes Patton et al 17 Yes Yes Yes Yes Yes Nair et al 70 No* Marrero et al 103 Yes Ohata et al 74 Yes *Steatosis was a risk for HCC in alcoholic and cryptogenic cirrhosis only. Abbreviation: BMI, body mass index.…”
Section: Steatosis Influences the Progression Of Fibrosis In Chronic Hcvmentioning
confidence: 99%
“…Data suggest that fixed, rather than weight-based dosing, irrespective of the type of interferon, leads to a decreased response to therapy in obese patients. Bressler et al 37 showed in a retrospective trial that BMI was associated independently with a decreased SVR in patients, although only a small number of patients received peginterferon alfa-2a at standard dose, and none of these patients were given ribavirin. However, pharmacokinetic studies of peginterferon alfa-2a have shown that serum levels of drug are higher at all time points than the weight-based peginterferon alfa2b.…”
Section: Diminished Effectiveness Of Antiviral Therapymentioning
confidence: 99%
“…Thus, the majority of SR patients are under 40 years old and have normal BMI and low baseline HCV RNA level, along with non-1 HCV genotypes and accelerated viral decay in the early periods of therapy. [2][3][4][5] In addition to the various factors enumerated above, documentation of higher SR rate in European Americans than African Americans has highlighted the ethnic differences, most likely due to genetic heterogeneity or increased occurrence of HCV genotype 1 in black people. Pharmacogenetic studies should be useful in elucidating such individual and ethnic disparities in response to HCV therapy.…”
Section: Heterogeneity In Response To Hcv Therapymentioning
confidence: 99%